2012
DOI: 10.1080/02701367.2012.10599139
|View full text |Cite
|
Sign up to set email alerts
|

Historical Perspective and Current Status of the Physical Education Graduation Requirement at American 4-Year Colleges and Universities

Abstract: This study gives an overview of the history of required physical education in America's 4 year colleges and universities and provides an update on the requirement status. After randomly identifying 354 institutions, we searched their respective websites to determine whether physical education was a requirement to earn a baccalaureate degree. The major finding was that the physical education requirement declined from an all-time high of 97% in the 1920s and 1930s to an all-time low of 39.55% in 2010. Given soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 46 publications
1
68
0
Order By: Relevance
“…Remarkably, though, physical activity educators have to continually justify their existence. This is especially apparent at the college or university level, where physical activity education requirements have declined steeply over the past 80 years and are now at an all-time low, with less than 40 percent of four-year institutions having a physical activity requirement (Cardinal, Sorensen, & Cardinal, 2012).…”
Section: Physical Activity Education's Contributions To Public Healthmentioning
confidence: 99%
“…Remarkably, though, physical activity educators have to continually justify their existence. This is especially apparent at the college or university level, where physical activity education requirements have declined steeply over the past 80 years and are now at an all-time low, with less than 40 percent of four-year institutions having a physical activity requirement (Cardinal, Sorensen, & Cardinal, 2012).…”
Section: Physical Activity Education's Contributions To Public Healthmentioning
confidence: 99%
“…Not only are periodic assessments necessary to understand secular trends, assessments are also necessary to understand different policy arrangements for the delivery of these courses (i.e., elective vs. required), as this may affect students' self-determined physical activity behavior. Because of observed declines in physical activity education requirements at the tertiary level in the United States (Cardinal et al, 2012), the now predominant elective policy arrangement appears to be limiting the potential reach and societal value of such courses (Cardinal, in press). This study also suggests that it shifts the focus, especially for women enrolled in these courses, toward extrinsic, personal benefits (i.e., improving and maintaining fitness, rather than learning a skill and having fun, as previous studies found).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, students under an elective physical activity course policy may have more autonomous motivation when taking part in physical activity classes (Hensley, 2000;Issue, 2000). Given a mixture of elective and required physical activity course policies across American colleges and universities (Cardinal, Sorensen, & Cardinal, 2012), there may be a previously unidentified commingling of students' reasons and motivation for enrolling in physical activity classes.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of this requirement was based on the effort to help students maintain their health and offset academic strain encompassed by the underlying belief that a sound physical constitution was essential to reach intellectual efficiency (Cardinal, Sorensen, & Cardinal, ). The tradition of requiring physical education has decreased over time and as of 2010, only 39.6% of colleges have an exclusive physical education requirement (Cardinal et al., ). Physical education courses also evolved over the past century to include both physical activity and various other health‐related concepts.…”
Section: Changes In Physical Education Courses In Collegementioning
confidence: 99%
“…One present challenge is that the criteria for health education courses are quite variable and courses may focus more on didactic learning rather than having students engage in actual physical activity. Interestingly, private colleges more often required physical education for a bachelor's degree compared to public colleges or universities (Cardinal et al., ).…”
Section: Changes In Physical Education Courses In Collegementioning
confidence: 99%